A case of bacteremia caused by Dialister pneumosintes and Slackia exigua in a patient with periapical abscess. (April 2016) - Lee, Min Young; Kim, Young Jin; Gu, Hyun Jung; Lee, Hee Joo
Abstract: Dialister pneumosintes and Slackia exigua are both obligatory anaerobe and known to be associated with periodontal diseases and other oral infection. We report a case of blood stream infection caused by D . pneumosintes and S . exigua . This occurred in a 78-year-old female patient that presented with general weakness and fever. We revealed that she had a periapical absecess. The blood culture was positive for D . pneumosintes and S . exigua ; however, identifying them was challenging. Ultimately, 16S rRNA sequencing was used to identify the organisms. The patient recovered after being treated with ceftriaxone and clindamycin. To the best of our knowledge, this is the first report of bacteremia caused by mixed infection of D . pneumosintes and S . exigua . Highlights: We report a bacteremia caused by Dialister pneumosintes and Slackia exigua . These bacteria were expected to be originated from an acute periapical abscess. D . pneumosintes and S . exigua were identified successfully through 16S rRNA sequencing. Clinicians should consider oral site searching the origin of systemic infection.